THE INFLUENCE OF THE CORE LEARNING MODEL ON THE ABILITY OF MATHEMATIC CONCEPT COMPREHENSION OF STUDENTS OF HIGH SCHOOL - Anil Hakim Syofra Anil; Irma Irma; Hery Saputra (Universitas Cokroaminoto Palopo, 2023)
This study aims to determine the effect of the CORE learning model on the ability to understand mathematical concepts of Al-Ma'shum Kisaran Private High School students for the 2021/2022 academic year. This type of research is quasi-experimental with a Pretest-Posttest Control Group Design. The population in this study were all of class XI consisting of 4 classes. Sampling was done by simple random sampling technique. In class XI MIA-1 as the experimental class using the CORE learning model and XI MIA-2 as the control class using the Direct learning model. Based on the value of the ability to understand the concept obtained, the average value of the experimental class was 83,4838 while the control class was 73.6774. The analysis technique using the t-test is obtained and because it is accepted , so with the result that is accepted. Thus, it can be concluded that the students ability to understand mathematical concepts using the CORE model is better than the ability to understand students mathematical concepts using the Direct learning model.